Measurement of energy expenditure using a triaxial accelerometer and estimation of energy intake from dietary records during decathlon competition days - Yoshitake, R.; Yamagami, A.; Obayashi, T.; Ogata, H.; Omi, N. (American Journal of Sports Science, 2024)
Background: Energy requirement (ER) for a competition day depends on the amount of energy consumed. Planning energy intake strategies is particularly important for decathlon athletes, who compete in track and field events over two days. However, few studies have reported how decathletes manage their energy intake. The aim of this study was to estimate the total energy intake (TEI) and total energy expenditure (TEE) of decathletes during competition days, considering with specific factors related to energy balance (EB). Methods: Eight athletes were analyzed who completed the decathlon in official track and field events. The TEI was calculated using photographs of all the food and beverages consumed by the athlete. TEE was estimated using a triaxial accelerometer-based method. The EB was calculated by the difference between TEI and TEE. Results: Over the two competition days (48 hours), the TEE for decathlon athletes was 7,984±202 kcal, with a negative EB observed on Day 2. The physical activity level (PAL) exceeded 2.3 on each day of the competition. EB was more strongly associated with TEI/kg than with TEE/kg, and was negative on Day 2. Conclusion: Competition days for decathlon athletes involve high intensity exercise. On Day 2 of the competition and the following competition day, there might be an energy deficiency. It is necessary to focus on strategies for energy intake after the competition ends in the future.